Occupational Injury Surveillance Among Law Enforcement Officers Using Workers' Compensation Data, Illinois 1980 to 2008. Issue 6 (June 2016) - Holloway-Beth, Alfreda; Forst, Linda; Freels, Sally; Brandt-Rauf, Sherry; Friedman, Lee
Abstract : Objective: Injuries among law enforcement officers are common, but poorly understood; workers' compensation (WC) data are an underutilized tool for occupational surveillance. Methods: A stratified analysis of WC claims among four categories of law enforcement officers used descriptive techniques, linear and robust regression. Results: Eighteen thousand eight hundred ninety-two officers filed claims from 1980 to 2008. Correctional officers had the highest rates, with leading causes of falls and assaults; motor vehicle crashes were the most common cause of injury among state police. Total monetary compensation was lower for correctional officers, but was explained by lower time lost and lower average weekly wage. Conclusion: The rate and types of injuries varied by subgroups, with correctional officers having the majority of injuries, but lower severity. WC data elucidate causes and outcomes of occupational injuries, which can guide prevention.